Mesoscale model for thermal conductivity of concrete. (15th November 2015) - Zhang, Weiping; Min, Hongguang; Gu, Xianglin; Xi, Yunping; Xing, Yishan
Highlights: Influences of different factors on thermal conductivity of concrete were presented. The theory of composite materials was applied to calculate thermal conductivity. Porosity was chosen as a key parameter in a new thermal conductivity model. Interfacial thermal resistance was considered to predict thermal conductivity. Thermal conductivity models for unsaturated and damaged concrete were proposed. Abstract: Thermal conductivity of coarse aggregate, cement mortar as well as concrete were measured by means of a guarded hot plate apparatus and/or a transient plane source. Influences of sand ratio, type and volume fraction of aggregate, water–cement ratio, saturation degree and load level on thermal conductivity of concrete were investigated. By using the theoretical model for thermal conductivity of composite materials, interfacial thermal resistance between cement mortar and coarse aggregate were studied further. The results show that thermal conductivity of concrete increases with the increasing saturation degree, volume fraction and thermal conductivity of aggregate, but decreases with the increasing water–cement ratio and load level. And interfacial thermal resistance coefficient decreases with the increasing saturation degree; therefore, interfacial thermal resistance must be considered when calculating thermal conductivity of concrete. Finally, mesoscale models were established for thermal conductivity of undamaged concrete in dry and unsaturated states based on the Maxwell's model. In addition, a mesoscale model was proposed for thermal conductivity of damaged concrete; this model is based on the assumption that damaged concrete was isotropic and damaged phase was served as an insulator. Mesoscale models can be used to predict the effective thermal conductivity of concrete under different states and the predicted values were all in acceptable agreement with the experimental values.